Pengaruh Pelatihan dan Penggunaan Teknologi Informasi terhadap Kinerja Karyawan Dengan Kepuasan Kerja sebagai Variabel Intervening di PT DSL Dharmasraya Sawit Lestari - Rian Safitri; Fitri Yeni; M Afuan (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
With work satisfaction serving as a mediator, this research intends to examine the impact of training and IT usage on employee performance at PT Dsl Dharmasraya Saawit Lestari. A survey and accompanying questionnaire were used to gather data from a sample of one hundred participants. Structured equation modeling makes use of SmartPLS 3 for its analysis.Training has a favorable and statistically significant effect on work satisfaction, according to the studies conducted. Information technology has a favorable and substantial effect on contentment in one's work life. Employee performance is positively and significantly impacted by training. In a small but favorable way, IT affects productivity in the workplace. Employee performance is greatly affected by how satisfied they are with their employment. The impact of training on employee performance is moderated by job happiness. An individual's level of contentment with their work life moderates the relationship between IT and productivity.